Hardiness as a mediator between perceived stress and happiness in nurses. Issue 9 (25th March 2014) - Abdollahi, A.; Abu Talib, M.; Yaacob, S. N.; Ismail, Z.
<x xml:space="preserve">Abstract</x> Accessible summary The relevance of the study of happiness and stress in nurses has been emphasized. In this sense, the intelligent use of hardiness is enable nurses to cope better with stress and contribute to being happier. This study aimed to examine the relationship among hardiness, perceived stress, and happiness in nurses. Moreover, we examined the mediator role of hardiness on the relationship between perceived stress and happiness in nurses. Our study revealed that hardi‐attitude nurses evaluate situations as less stressful which results in a higher happiness. This study showed hardiness as being a protective factor against perceived stress and a facilitating factor for happiness in nurses. The findings could be important in training future nurses so that hardiness can be imparted, thereby giving them the ability to control their stress. Abstract Nursing is a stressful occupation with high levels of stress within the health professions. Given that hardiness is an important construct to enable nurses to cope better with stress and contribute to being happier; therefore, it is necessary we advance our knowledge about the aetiology of happiness, especially the role of hardiness in decreasing stress levels and increasing happiness. The present study sought to investigate the role of hardiness as a mediator between perceived stress and happiness. The participants, comprising 252 nurses from six private hospitals in Tehran, completed the Personal Views Survey, the Perceived Stress Scale, and the Oxford Happiness Inventory. Structural Equation Modelling (SEM) was used to analyse the data and answer the research hypotheses. As expected, hardiness partially mediated between perceived stress and happiness among nurses, and nurses with low levels of perceived stress were more likely to report greater hardiness and happiness. In addition, nurses with high levels of hardiness were more likely to report happiness. This study showed hardiness as being a protective factor against perceived stress and a facilitating factor for happiness in nurses. The findings could be important in training future nurses so that hardiness can be imparted, thereby giving them the ability to control their stress.